PENGARUH BEBERAPA CARA PEMANGKASAN TAJUK TERHADAP PERTUMBUHAN DAN PRODUKSI GAMBIR (Uncaria gambir (Hunter) Roxb) - ZULKIFLI HASAN (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
Effect of pruning on the growth and yield of gambir (Uncaria gambir)Gambir is harvested by pruning Uie branches, twigs and leaves. Improving pruning method in harvesting Ihe crop may cnchancc (o increase the yield of dry gambir where al prcscnl (he yield was 632 kg/ha. Therefore, different techniques of pruning were studied, including : table, clean, and deep prunnings, and pruning technique adapted by farmers as the control The study was conducted in the Laing Experiment Farm, Solok, from April 2000 to February 2001. The experiment was designed as a randomized block in 6 replicates. Results showed that pruning conducted al harvest improved the growth of plant and increase the yield of dry gambir. The highest yield of dry gambir compared with table pruning produced 735,25 kg/ha, significantly higher than deep pruning (371, 25 kg/ha), clean pruning (464.40 kg/ha) or pruning adapted by farmer (521 kg/ha). The last three methods were not signiicantly different in terms of the yield.